MEANING ANALYSIS AND DYNAMIC EQUIVALENCE - Nasibullayeva Xalimaxon; Axmedov Azimjon (TADQIQOTLAR, 2025)
Abstract Translation is not a mere act of substituting words from one language to another; it involves an in-depth understanding of linguistic and cultural components. This article examines the significance of meaning analysis and dynamic equivalence in translation theory and practice. Meaning analysis ensures a comprehensive grasp of both denotative and connotative meanings in a source text, while dynamic equivalence, as proposed by Eugene Nida, aims to reproduce a similar response in the target audience. The study concludes that dynamic equivalence is most effective when grounded in detailed meaning analysis, especially in culturally rich or emotionally nuanced texts.